2013
DOI: 10.1159/000351033
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Aspects of Neonatal Extracorporeal Membrane Oxygenation: A Review

Abstract: Background: Neonatal extracorporeal membrane oxygenation (ECMO) is a lifesaving therapeutic approach in newborns suffering from severe, but potentially reversible, respiratory insufficiency, mostly complicated by neonatal persistent pulmonary hypertension. However, cerebral damage, intracerebral hemorrhage as well as ischemia belong to the most devastating complications of ECMO. Objectives: The objectives are to give insights into what is known from the literature concerning cerebral damage related to neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…Some have suggested that loss of pulsatile arterial flow during VA ECMO disturbs cerebral autoregulation and contributes to the increased risk of intracranial hemorrhage. 24 Lower daily fibrinogen concentration was also independently associated with intracranial hemorrhage in our study population. Previous studies both confirm and refute this finding.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Some have suggested that loss of pulsatile arterial flow during VA ECMO disturbs cerebral autoregulation and contributes to the increased risk of intracranial hemorrhage. 24 Lower daily fibrinogen concentration was also independently associated with intracranial hemorrhage in our study population. Previous studies both confirm and refute this finding.…”
Section: Discussionmentioning
confidence: 51%
“…For example, neonates receiving ECMO for respiratory diagnoses may experience prolonged periods of hypoxia and hypercarbia in the pre-ECMO phase of illness that can disrupt cerebral autoregulation and increase the brain's vulnerability to hyperemia and hemorrhage during the ECMO course. 23,24 In our study, 80% of neonates treated with therapeutic hypothermia during ECMO had a primary respiratory diagnosis and 65% had persistent pulmonary hypertension. In a recent study of neonates treated with standard ECMO for persistent pulmonary hypertension, 34% developed intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 59%
“…Some studies in pediatric ECMO population have demonstrated increased risk of mortality and intracranial hemorrhage with VA ECMO compared to VV ECMO [14][15][16]. The loss of pulsatile arterial flow during VA ECMO could disturb cerebral autoregulation and contribute to increased risk of intracranial hemorrhage [17]. The most common indication for ECMO in infants with HIE is respiratory pathology [11] and thus initiation with VV ECMO should be feasible in the majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulation is required to prevent the formation of thrombi within the ECMO circuit. Together with altered haemodynamics and damage to, or occlusion of, the neck vessels, there is an increased risk of neurologic complications, including intracerebral haemorrhage and ischaemic/embolic infarction [2].…”
Section: Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…Haemorrhage Intracranial haemorrhage is the most frequent neurologic complication in neonates receiving ECMO support [11], the majority of cases occurring within 72 h of initiation of ECMO support [6]. It is notable that most nonsurvivors of ECMO support die from intracranial haemorrhage rather than their primary cardiorespiratory disease [2]. The mastoid fontanelle provides a window (oblique coronal view) to examine the cerebellum and its vermis, the inferior temporal lobes, the midbrain and the cranial portion of the spinal cord in the same 3-day-old boy as in Fig.…”
Section: Abnormal Findingsmentioning
confidence: 99%